Genomic organization of alpha satellite DNA on human chromosome 7: evidence for two distinct alphoid domains on a single chromosome. - Waye, J S (Mol Cell Biol, 1987)
A complete understanding of chromosomal disjunction during mitosis and meiosis in complex genomes such as the human genome awaits detailed characterization of both the molecular structure and genetic behavior of the centromeric regions of chromosomes. Such analyses in turn require knowledge of the organization and nature of DNA sequences associated with centromeres. The most prominent class of centromeric DNA sequences in the human genome is the alpha satellite family of tandemly repeated DNA, which is organized as distinct chromosomal subsets. Each subset is characterized by a particular multimeric higher-order repeat unit consisting of tandemly reiterated, diverged alpha satellite monomers of approximately 171 base pairs. The higher-order repeat units are themselves tandemly reiterated and represent the most recently amplified or fixed alphoid sequences. We present evidence that there are at least two independent domains of alpha satellite DNA on chromosome 7, each characterized by their own distinct higher-order repeat structure. We determined the complete nucleotide sequences of a 6-monomer higher-order repeat unit, which is present in approximately 500 copies per chromosome 7, as well as those of a less-abundant (approximately 10 copies) 16-monomer higher-order repeat unit. Sequence analysis indicated that these repeats are evolutionarily distinct. Genomic hybridization experiments established that each is maintained in relatively homogeneous tandem arrays with no detectable interspersion. We propose mechanisms by which multiple unrelated higher-order repeat domains may be formed and maintained within a single chromosomal subset. IMAGES: